2020
DOI: 10.3390/antiox9070614
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Health-Promoting Functionality of Rye Bread by Fortification with Free and Microencapsulated Powders from Amelanchier alnifolia Nutt

Abstract: This study established the appropriate amounts of a functional Saskatoon berry fruit powder in fortified rye bread acceptable to consumers and determined the potential relative bioaccesibility of bioactive compounds exhibiting antioxidant activity, and enzymatic in vitro inhibitory activity against lipoxygenase, cyclooxigenase-1, cyclooxigenase-2, acetylcholinesterase, pancreatic lipase α-glucosidase, and α-amylase, as well as the relative digestibility of nutrients. The content of polyphenolic compounds and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 48 publications
0
12
0
2
Order By: Relevance
“…Also, the interactions of polyphenols (mainly anthocyanins and procyanidins) with the food matrix reduced the polyphenols bioaccessibility, thus reducing the number of polyphenols potentially available for enzyme inhibition [ 29 ]. In another work, Lachowicz et al [ 30 ] showed that the enrichment of rye breads with the 3% of a berry fruit powder determined a strong increase in the bioaccessibility of anthocyanins following an in vitro digestion process, whereas the least bioaccessible fraction was that of flavan-3-ols.…”
Section: Resultsmentioning
confidence: 99%
“…Also, the interactions of polyphenols (mainly anthocyanins and procyanidins) with the food matrix reduced the polyphenols bioaccessibility, thus reducing the number of polyphenols potentially available for enzyme inhibition [ 29 ]. In another work, Lachowicz et al [ 30 ] showed that the enrichment of rye breads with the 3% of a berry fruit powder determined a strong increase in the bioaccessibility of anthocyanins following an in vitro digestion process, whereas the least bioaccessible fraction was that of flavan-3-ols.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, when considering the incorporation of polyphenols, the encapsulation technique represents a valid solution to overcome their sensibility to high processing temperatures and alkaline pH as well as the possible undesirable increase in astringency and bitterness in the fortified products. Bread antioxidant properties and the content of phenolic compounds have been enhanced using extracts derived from several sources, such as Garcinia cowa fruit [10,42], green tea [43], Saskatoon berry fruit [44,45], and the bark of soybeans, onion husks, and young hawthorn shoots [46].…”
Section: Phenolic Extractsmentioning
confidence: 99%
“…У зв'язку з цим пошук нових видів рослин, які є цінними джерелами біологічно активних сполук (Khromykh et al, 2018a(Khromykh et al, , 2018b, є одним з актуальних завдань раціонального використання рослинних ресурсів. Виходячи з цього, інтродукція та селекція таких рослин, технологія їх вирощування, способи вилучення комплексу біологічно активних речовин та створення на його основі, наприклад, харчових добавок нового покоління являють собою перспективний науковий напрямок (Brindza et al, 2019;Horčinová Sedláčková et al, 2019;Lachowicz et al, 2020). Отже, багатовекторне позиціонування ботанічного саду як універсального екологічного ресурсу -це світовий тренд, складова парадигми сучасного ботанічного саду, яка пов'язана з трансформацією його матеріальних і нематеріальних ресурсів з метою збереження біорізноманіття, підвищення якості життя дюдей, покращення їх добробуту.…”
unclassified